The Transmission of Religious Beliefs across Generations: Do Grandparents Matter? - Copen, Casey E.; Silverstein, Merril (Journal of Comparative Family Studies)
Despite substantial changes in the family's structure over the past four decades, parents continue to exert a lasting imprint on the religious ideology and commitments of their children. However, research on the intergenerational transmission of religious beliefs, values and practices to younger generations has not included the ways in which grandparents—particularly grandmothers—influence the religiosity of youth. Drawing on the Longitudinal Study of Generations (LSOG), we examined the extent to which grandmothers and parents influence the religious beliefs of adolescent and young adult grandchildren. First, we asked whether grandmothers influence the religious beliefs of their grandchildren independently of the grandchildren's parents. Our results indicated that grandmothers and grandchildren resembled one another on a series of statements conveying conservative religious beliefs and attitudes. Second, we examined patterns of religious transmission from grandmothers and parents to their children. We found that grandmothers transmitted their religious beliefs to grandchildren more strongly when mothers were more religious. Our third research question asked whether parental divorce weakens religious continuity across generations. We found that divorce adversely affected religious transmission from mothers to their children, but not from fathers and grandmothers. In addressing our fourth research question about the role of gender in religious transmission, we found that religious similarity between grandmothers and granddaughters was particularly strong. In general, our study showed a significant degree of religious similarity across three generations in the family, and offers an expanded view of religious socialization by considering grandmothers as active contributors to the religious beliefs of contemporary young adults. Reprinted by permission of the publisher.